THE SAMADATA AND SEHATI PROGRAMS IN FOSTERING POLITE AND RELIGIOUS CHARACTER AMONG STUDENTS AT SAHABAT AL-QUR'AN INTEGRATED ISLAMIC ELEMENTARY SCHOOL (SDIT) DOMPU - Eila Mawar Fitria; Nasaruddin; Agus Salam (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the implementation of the SAMADATA and SEHATI programs in fostering polite and religious character among students at SDIT Sahabat Al-Qur’an Dompu and to explore how local wisdom and religious habituation are integrated within the school’s character education practices. This study employed a qualitative descriptive approach with a case study design. Data were collected through interviews, observations, and documentation involving school stakeholders and program-related activities. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, supported by triangulation techniques to enhance data credibility. The findings indicate that the SAMADATA program contributes to the cultivation of polite character through the integration of Dompu local wisdom, particularly the expressions santabe, mada, ita, and iyota, into daily school interactions and learning activities. The study also suggests that the SEHATI program supports the development of religious character through the habituation of ritual and social worship practices conducted at school and reinforced through parental involvement at home. The internalization process appears to involve cognitive understanding, affective engagement, and behavioral practice, although the extent of its influence may vary among students. This study was conducted in a single Islamic elementary school and relied on qualitative evidence derived from interviews, observations, and documentation. Therefore, the findings are context-specific and cannot be generalized to other educational settings. Future studies are recommended to involve multiple schools, a broader range of participants, and mixed-method approaches to examine character development more comprehensively and to validate the applicability of the identified practices in different contexts. This study contributes to the literature on Islamic character education by highlighting the integration of local cultural values and religious habituation within a school-based character education framework. It offers a contextual perspective on how Dompu local wisdom and Islamic practices can be incorporated into everyday school culture to support the development of polite and religious character among elementary school students.